ANALISIS RASIO KEUANGAN DAN FAKTOR NON KEUANGAN YANGMEMPENGARUHI AUDITOR DALAM MEMBERIKAN OPINI AUDITGOING CONCERN PADA AUDITEE - Veri Anang Putra; Erni Suryandari (Universitas Muhammadiyah Yogyakarta, Indonesia, 2010)
In this study, we attempt empirically to investigate the effect between financial ratios (liquidity, profitability, solvability, activity, leverage, sales growth, market value, size) and non financial factors (public accountant reputation, previous audit report, auditor-client tenure, audit lag) on going concern audit opinion. Sample of 148 manufacturing companies listed at Jakarta Stock Exchange from 2004-2007. Logistic regression is used to examine hypothesis.The results indicated that liquidity, profitabilitas, and previous audit lag are significantly affect the going concern audit opinion. On the hand, solvability, activity, leverage, sales growth, market value, size, public accountant reputation, auditor-client tenure, audit lag does not affect on going concern audit opinion.